2016
DOI: 10.1093/cid/ciw700
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection: Prognostic Value of Maternal DNAemia at Amniocentesis

Abstract: Maternal viremia at amniocentesis is associated with a 3-fold greater chance of congenital infection, but it is not correlated with symptomatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
3
25
0
1
Order By: Relevance
“…The value of viral DNA detection and quantification in blood, saliva, or urine to help determine the timing of maternal infection, or to estimate the risk of fetal transmission, is not yet established. Notably, two studies have demonstrated that persisting levels of maternal DNAemia during primary CMV infection at the moment of amniocentesis correlate with a high risk of CMV transmission to the fetus (26,27), whilst one other study has shown that the presence of CMV DNA in maternal urine and maternal blood correlated with transmission of CMV to offspring (28).…”
Section: Serologic and Molecular Testing For Maternal CMV Infectionmentioning
confidence: 99%
“…The value of viral DNA detection and quantification in blood, saliva, or urine to help determine the timing of maternal infection, or to estimate the risk of fetal transmission, is not yet established. Notably, two studies have demonstrated that persisting levels of maternal DNAemia during primary CMV infection at the moment of amniocentesis correlate with a high risk of CMV transmission to the fetus (26,27), whilst one other study has shown that the presence of CMV DNA in maternal urine and maternal blood correlated with transmission of CMV to offspring (28).…”
Section: Serologic and Molecular Testing For Maternal CMV Infectionmentioning
confidence: 99%
“…The biological VT to the fetus for CMV appears to be increased with a positive maternal viremia (OR 3.06, 95% CI 1.41-6.64) [52] and the transmission evidence with the identification of fetal "disruptive" anomalies by US [54]. A negative (undetected) maternal CMV viremia result has a reported viral VT rate of 15-20% [52,53].…”
Section: Questionmentioning
confidence: 97%
“…The possibility of an increased preterm birth mechanism associated with intrauterine viral infection in the late second and third trimester alone has limited data to support this perinatal risk [19,46,47]. Table 3 summarizes the published literature for maternal infection cohorts and the outcomes for unintended fetal loss and evaluations to determine the possibility of fetal VT [48][49][50][51][52][53][54][55][56]. The "pooled" procedure-related fetal loss risk estimate for infectious diagnostic amniocentesis procedures is estimated at 1.5% (18/1,187) -0.8% from varicella (1/127), 0% from HCMV (0/458), and 2.8% from toxoplasmosis (17/602).…”
Section: Questionmentioning
confidence: 99%
See 2 more Smart Citations